Pedagogia teatrale e mondo-scuola - Aurora Caporali (Mimesis Journal, 2022)
The aim of this essay is to present an idea of theatre pedagogy for the use of theatre in the educational context (first-grade secondary school): this work is offering a reflection, with no claim to exhaustiveness, but with the promise of a coherent exercise, aimed at guiding the structuring of articulated and effective didactic-theatre projects. There are numerous studies on the pedagogy of theatre: among the most recent, Mango’s experience appeared as a monograph in “Costellazioni”, issue 24, Theatre and pedagogical processes, to which must be added Rivoltella’s latest volume Drammaturgia didattica, as well as the text edited by Pontremoli Elementi di teatro educativo, sociale e di comunità. In such an encouraging and stimulating framework we can move not only in a reconnaissance logic, but also in a propositional direction, also interpreting the Italian ministerial indication of Law 107/2015 (paragraph 181) on theatre education in schools. The essay will start from the definition of the third millennium school’s didactic needs and the opportunities offered by the object Theatre. Ultimately, an annotated operational project is presented, through the classic scheme of the interdisciplinary learning unit.